Supplement to Common Knowledge

Proof of Proposition 2.4

Proposition 2.4.
If ω ∈ K*N(E) and EF, then ω ∈ K*N(F).

If EF, then as we observed earlier, Ki(E) ⊆ Ki(F), so

K1N(E) =  

Ki(E) =  

Ki(F) = K1N(F)

If we now set E′ = KnN(E) and F′ = KnN(F), then by the argument just given we have

Kn+1N(E) = K1N(E′) ⊆ K1N(F′) = Kn+1N(F)

so we have mth level mutual knowledge for every n ≥ 1.

Hence if ω ∈

KnN(E) then ω ∈

KnN(F). □

Return to Common Knowledge

Copyright © 2013 by
Peter Vanderschraaf
Giacomo Sillari <>

Open access to the SEP is made possible by a world-wide funding initiative.
The Encyclopedia Now Needs Your Support
Please Read How You Can Help Keep the Encyclopedia Free